IMPACT OF JOB SATISFACTION IN PRIVATE ORGANIZATIONS - A CASE STUDY OF PANIPAT DISTRICT - Monika Devi; Dr. Kuldeep Kumar (Innovative Research Thoughts, 2023)
In the present competitive era, It is not feasible for any organization to survive without efficient and enthusiastic employees. Although some researches enthralled on job satisfaction and employee performance, empirical work on the determinants of job satisfaction and its effect on performance especially in private companies is meager. This research attempts to fill the gap by using Private company in the Panipat District as a case study. The study reviewed literature on the concepts of job Satisfaction, its determinants and performance. The study employed quantitative and qualitative methodology. Data was assorted through the questionnaire and an in-depth interview.